Successful Self-Management: A psychologically sound approach to personal effectiveness - Paul R. Timm (Fifty-Minute series., 2004)
Somewhere underneath the daily cycle of work, family, and life in general, you possess a value system, a set of bone-deep beliefs that powers everything you do. Successful self-management is about tapping into your most desired goals and maximizing your time, energy, and resources toward achieving them. Learning to manage all the different areas of your life successfully is an ongoing process, but you can approach each new challenge with a clear sense of purpose. The key is in connecting your core value to your goals. SUCCESSFUL SELF-MANAGEMENT presents you with five building blocks for success: perspective, purpose, personality, planning, and productivity. With each new chapter, you will learn to apply what you have learned so you can get started right away. Say you\\\\\\\\\\\\\\\'d like more financial security, or career success - this book provides you with clear tips and planning worksheets to get you organized